2018
DOI: 10.1111/bjd.17276
|View full text |Cite
|
Sign up to set email alerts
|

Pachyonychia congenita: a case report of a successful treatment with rosuvastatin in a patient with a KRT6A mutation

Abstract: Summary Pachyonychia congenita (PC) is a rare autosomal dominant disorder characterized by nail dystrophy and palmoplantar keratoderma with severe plantar pain affecting quality of life. There is no effective treatment. Heterozygous mutations in the keratin genes KRT6A, KRT6B, KRT6C, KRT16 and KRT17 have been reported as a cause of PC. Herein we present a female patient with an amino acid substitution mutation in KRT6A (c.1381G>A, p.Glu461Lys in exon 7) and classic features of PC associated with oral leucokera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…The experience of physicians collaborating with the Pachyonychia Project in using statins in PC is mixed, with a few patients experiencing improvement in plantar pain and some experiencing no change . In this issue of the BJD , Abdollahimajd and colleagues from the Shahib Beheshti University of Medical Sciences in Iran, report a case study of an 8‐year‐old female patient with PC with a mutation in KRT6A treated with rosuvastatin 5 mg daily with a reduction in both plantar hyperkeratosis and pain . The patient was treated for 6 months with a nine‐point drop in Children's Dermatology Life Quality Index score and a reduction in hyperkeratosis and blistering.…”
mentioning
confidence: 99%
“…The experience of physicians collaborating with the Pachyonychia Project in using statins in PC is mixed, with a few patients experiencing improvement in plantar pain and some experiencing no change . In this issue of the BJD , Abdollahimajd and colleagues from the Shahib Beheshti University of Medical Sciences in Iran, report a case study of an 8‐year‐old female patient with PC with a mutation in KRT6A treated with rosuvastatin 5 mg daily with a reduction in both plantar hyperkeratosis and pain . The patient was treated for 6 months with a nine‐point drop in Children's Dermatology Life Quality Index score and a reduction in hyperkeratosis and blistering.…”
mentioning
confidence: 99%
“…Oral retinoids successfully reduced callus thickness in some individuals with PC, but like rapamycin, adverse side‐effects including increased pain prevent oral retinoids from being a viable long‐term treatment for PC . Statins can also downregulate KRT6A expression, but so far only oral rosuvastatin has been shown to be effective in a single case of K6a‐based PC . Finally, injections of botulinum toxin (Botox) into plantar calluses improved plantar blistering and pain associated with PC–PPK lesions, but injections are costly and must be performed under anaesthesia.…”
Section: Limitations Of Past and Current Therapeutic Strategies For Pmentioning
confidence: 99%
“…Some small studies have reported pain relief and improvement in quality of life in individuals who received off‐label treatment with rapamycin or statins . Consequently, the Food and Drug Administration recently granted fast‐track designation for a trial of high‐strength topical rapamycin to treat PC.…”
Section: Therapeutic Approaches To Pain In Pachyonychia Congenitamentioning
confidence: 99%